Intervalling and Diversification Effect on Skewness and Kurtosis of Stock Returns: A case of Hong Kong - Gordon Y. N. Tang (Asian Academy of Management Journal, 1997)
Intervalling and Diversification Effect on Skewness and Kurtosis of Stock Returns: A case of Hong Kong (PDF not available)